Promoting global virtual teams across the globe: Cross-cultural challenges and synergies - Zakaria, Norhayati; Al Safi, Ghadeer; Williams, Nigel (IGI Global, 2013)
This chapter presents a preliminary understanding of cross-cultural challenges and synergistic experiences of multicultural students engaged in Global Virtual Teams (GVTs).In this case study, we introduce the GVT structure as a novel learning platform which utilizes Computer Mediated Communication (CMC) tools as part of its virtual-based learning.We administer the case study with 30 students (n=30) in the United of Emirates (UAE) who engage in GVTs across the globe—encompassing 26 universities and 22 countries.Qualitative data is collected in the form of documents—reflective reports of the students’ experiential learning over a 10-week period.We content analyse the reports based on the thematic analysis with two distinctive categories—cultural challenges and cultural synergies based on the first seven weeks of the experiential learning process.In this study, we find that students experienced challenges such as managing technical difficulty, language barriers, deteriorating motivations, geographical distance, time differences, and non-committed and unresponsive attitude.However, students also experience synergies from the GVTs such as strong relationships and continued friendships, formation of emergent leadership, learned diverse managerial styles and competencies skills, varied use of varied CMC tools, and international exposure to diverse cultures without the need to travel abroad.